ANATOMI KEABSAHAN BUNGA BANK DALAM PERSPEKTIF TEORI LIMIT MUHAMMAD SYAHRÛR - Dadang Abdul Qadir (Asy-Syari'ah, 2014)
Riba is an excess of the capital, which is including all types of loans that used a lot or a little an extra. The majority of Muslim stated that interest and usury (riba) are the same, so that the interest became haram. Nevertheless, Muhammad Syahrûr said that the interest is not usury (riba), for not reaching 100% of the capital invested. He used a different methodology than the majority of Muslim scholars. He developed his own methodology in making a law. One of them is the theory of limits. The term limits (hudûd) is used referring to the sense of the limits of the provisions of God that should not be violated, but there is a region for ijtihâd which are dynamic, flexible, and elastic. The method used in this paper is descriptive, whereas technical for collecting data is literature study, especially the book written by Muhammd Syahrûr  , namely al-Kitâb wa al-Qur’ân: Qirâ’ah Mu‘âshirah.